Spatial-temporal differentiation of eolian sediments in the Yarlung Tsangpo catchment, Tibetan Plateau, and response to global climate change since the Last Glaciation - Ling, Zhiyong; Yang, Shengli; Wang, Xin; Wang, Jianping; Xia, Dunsheng; Chen, Fahu (Geomorphology (Amsterdam, Netherlands), 2020)
Eolian sediments, an important paleoenvironmental archive, are widespread in the Yarlung Tsangpo River (YTR) valley of the southern Tibetan Plateau (TP), but their chronology and spatial-temporal differentiation are poorly understood. And it is not clear whether eolian accumulation is controlled by global climate changes, or local paleoenvironment, or both. In this study, we applied quartz OSL dating to 30 eolian sediment samples (sandy loess and eolian sand) from eight profiles in the YTR catchment. Our new dates were combined with 72 previously published eolian sediment ages (OSL/TL and 14C) for the YTR catchment to analyze the response of eolian accumulation to paleoenvironmental changes. The overall dataset has eolian accumulation spanning the period from the Last Interglacial through to the Little Ice Age, ranging from 84.6 ± 8.7 ka BP (possibly as old as 118 ± 11 ka BP) to 0.4 ± 0.1 ka BP, with most occurring since the Late Glacial Period (15 ka BP), which suggests that the preservation of eolian deposits is controlled by geologic recirculation. Probability density function distributions (PDFs) of eolian ages from different parts of the YTR catchment show different age clusters, suggesting that factors controlling eolian accumulation vary across the catchment, so that spatial-temporal disparities are inherent in the system. To investigate the effect of regional and global paleoclimate since the Last Glacial Maximum (LGM) on eolian deposition processes in the YTR, we compared the PDF of ages from the combined dataset with a range of paleoclimate proxies. The PDF shows significant fluctuations since the LGM, including the Younger Dryas cold event. There is no consistent eolian sediment response to changes of the 30°N summer insolation, Asian Summer Monsoon, and westerlies. Phases of strong eolian sediment accumulation in the YTR basin do not show a simple correspondence with the classical global climate curve, suggesting that eolian processes in the alpine valley environment may be modified by local responses to these changes. •Ages of eolian deposits in the Yarlung Tsangpo River (YTR) catchment are compared.•Most of the ages are since 15 ka BP, ranging from 0.4±0.1 to 118±11 ka BP.•Spatial-temporal disparities of eolian accumulation in the YTR are pointed out.•A relation between eolian accumulation and paleoenvironment is provided.